Potential of harnessing incident solar energy in building shading device for thermal application - Ng, Khai Mun (2018)
The recent trend of integrating a solar energy system in building has become a sustainable solution for energy conservation. This work proposed an alternative philosophy of solar absorber system, which is harnessing the incident solar energy on the building shading device. The existing literature mainly discussed the performance of shading devices in term of expelling solar incident ray, excluding the potential of energy collection. There is limited investigation on the energy harnessing through shading device under the tropical skies. Besides, most of the building integrated solar thermal models were developed and studied in higher latitude regions. The overall objective of this work is to develop a shading façade-integrated solar absorber system model and assess its performance under the hot tropical climate. Mathematical considerations of solar radiation model, shading façade-integrated solar absorber geometrical model and solar absorber model were resolved holistically in a segregated manner using MATLAB programming environment. The orientation, geometrical and thermal characteristics of the system model were analysed and assessed to configure the system model optimally. Numerical results showed that the optimum tilt angle of the shading façade-integrated solar absorber for maximum solar radiation interception was approximately 15°. According to the geometrical and thermal performance analyses, the configuration of two solar plates system with the dimensions of plate-to-cover spacing of 10 mm, plate thickness to width ratio of 0.15 and tube centre-to-centre distance of 8.2 cm was the optimum option. It has resulted in the maximum effective area of exposure to solar ray, minimum overall heat loss coefficient and optimum heat removal factor valued at 98.9%, 8.5951 W/(m2K) and 0.898, respectively. A prototype of the complete system model was fabricated according to the outcomes of the numerical simulations. To confirm its performance, outdoor experiments were conducted in daytime for 139 days under the actual tropical sky. The outdoor field test has demonstrated that the system model was principally dependent on the available global irradiance and its performance was impaired by the high occurrence of afternoon rain. On average, the system model was capable to achieve the daily system efficiency of 50.5%, maximum daily water temperature attained at 48.9 °C and solar water heating rate of 2.9 °C/hr. Findings showed that the system model could perform most frequently at the daily system efficiency ranging from 45% to 60% and the maximum daily water temperature attained from 45 °C to 57 °C during the test period. Under the stagnant condition, the measured maximum temperatures of glass surface and absorber plate surfaces were 74.3 °C and 102.9 °C, respectively. Verification of results for the simulation and experimental data measurement were conducted; and they were in agreement.